Meta-analytic review of research on hostility and physical health. [article]. - Miller, Todd Q.
A new meta-analysis of research on hostility and physical health was conducted that includes 15 studies used in previous meta-analytic reviews and 30 new independent studies. Overall, the results suggest that hostility is an independent risk factor for coronary heart disease (CHD). For structured interview indicators of potential for hostility, the weighted mean r was .18. After controlling for other risk factors for CHD, the widely used Cook-Medley Hostility Scale and other cognitive-experiential measures were most predictive of all-cause mortality (weighted mean r = .16) and, to a lesser extent, CHD (weighted mean r = .08). Similar to other areas of research, the increased use of high-risk studies in recent years produced an increase in null findings. -- (from the author)